Being the Master of Myself : Pelatihan Emotional Intelligence untuk Meningkatkan Psychological Well-Being Asisten Dosen - Yuan Yovita Setiawan; Emilia Arliansyah (Universitas Islam Indonesia, 2021)
Assistant lecturers have a duty as students as well as have additional responsibilities as a bridge between lecturers and students. These heavy duties and obligations carried by assistant lecturer impacted their psychological well being. This training carries emotional intelligence as a variable that can improve the psychological well being of assistant lecturers. This research will use one group pre-post test experimental design. 21 people participated on this training. The t-test results showed a significance of .169 (p > .05) which meant there was no significant difference in psychological well being level after training. Some factors that influence the unsuccessful emotional intelligence training in improving psychological well being are the use of trait emotional intelligence models, duration of the training, stress levels and education levels of training participants.